Science-Based Inquiry Learning with Islamic Values to Improve Critical Thinking: Pembelajaran Berbasis Penyelidikan Ilmiah dengan Nilai-Nilai Islam untuk Meningkatkan Pemikiran Kritis - Fahyuni , Eni Fariyatul; Anggraini, Ria Resti (Adabiyah: Jurnal Pendidikan Islam, 2025)
General background: Critical thinking is an essential competency in 21st-century education, requiring learning models that actively involve students. Specific background: Elementary science education often remains teacher-centered, limiting opportunities for students to develop reasoning skills. Knowledge gap: Few studies in Indonesia have investigated the integration of Islamic values within inquiry-based science learning, particularly in fostering students’ critical thinking. Aims: This study aims to examine the role of science-based inquiry learning integrated with Islamic values in improving critical thinking among fourth-grade students. Results: Using a mixed-method design, findings indicate that the experimental class applying inquiry learning showed higher post-test scores and N-gain compared to the control class with conventional learning. Students actively engaged in investigations, discussions, and reflections while relating their learning to Qur’anic values. Novelty: The study uniquely integrates Islamic teachings with scientific inquiry to cultivate both cognitive and spiritual development. Implications: The findings suggest that inquiry-based learning contextualized with Islamic values can foster meaningful science learning while shaping students’ character and critical thinking abilities. Highlights : Integration of Islamic values with inquiry learning supports critical thinking. Students show higher achievement in inquiry-based classes. Inquiry learning provides meaningful cognitive and spiritual development. Keywords : Inquiry Learning, Science Education, Islamic Values, Critical Thinking, Mixed Methods